Open innovation and distributed innovation differents models of innovation? - Trentini, Anny Margaly Maciel (2012)
Innovation has becoming an irreversible process including several steps and aspects like financial, cultural and organizational. Several models of innovation have been reported in the literature, including the Open Innovation and Distributed Innovation model. This article presents concepts, features and examples of these two models of innovation and a proposal for analysis of these concepts, to see if is necessary to make the differentiation of the nomenclature of these models. As a result presents a table comparing the characteristics of each type of innovation discussed. It is observed that the models distributed and open innovation are an alternative approach to organizing for innovation, and whatever the choice, both models are being used with success.